Combinations of select menhaden fish meal and spray-dried plasma protein in the transition diet (11 to 15 lb) for the early-weaned pig - Bergstrom, J.R.; Owen, K.Q.; Nessmith, W.B. Jr; Richert, B.T.; Smith, J.W. II; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Early-weaned pigs (weaned at 7 to 14 d of age) that are managed in a conventional, one-site production system require a more complex diet in the transition phase (11 to 15 lb) than early-weaned pigs that are managed in a segregated early weaning (SEW), multiple-site, production system.
Keywords: Swine; Pigs; Growth performance; Fish meal; Plasma